2013
DOI: 10.1007/s12011-013-9728-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Chromium Content of Feedstuffs, Their Estimated Requirement, and Effects of Dietary Chromium Supplementation on Nutrient Utilization, Growth Performance, and Mineral Balance in Summer-Exposed Buffalo Calves (Bubalus bubalis)

Abstract: This study was conducted to determine the chromium content of different feedstuffs, their estimated requirement, and effect of dietary Cr supplementation on nutrient intake, nutrient utilization, growth performance, and mineral balance in buffalo calves during summer season. Levels of Cr was higher in cultivated fodder, moderate in cakes and cereal grains, while straw, grasses, and non-conventional feeds were poor in Cr content. To test the effect of Cr supplementation in buffalo calves, 0, 0.5, 1.0, and 1.5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
5
6
2
Order By: Relevance
“…Present findings indicated that inorganic trivalent Cr as CrCl 3 may be potentially effective in enhancing nutrient utilization in lactating buffaloes. However, our results contrast with those of Kumar et al [8] who stated that inorganic Cr supplementation in summer-exposed Murrah buffalo calves had no effect on nutrient digestibility. No effect of Cr supplementation on nutrient digestibility was in agreement with the findings of others [23, 31, 41].…”
Section: Nutrients Digestibility Nitrogen Utilization and Chromium contrasting
confidence: 99%
See 1 more Smart Citation
“…Present findings indicated that inorganic trivalent Cr as CrCl 3 may be potentially effective in enhancing nutrient utilization in lactating buffaloes. However, our results contrast with those of Kumar et al [8] who stated that inorganic Cr supplementation in summer-exposed Murrah buffalo calves had no effect on nutrient digestibility. No effect of Cr supplementation on nutrient digestibility was in agreement with the findings of others [23, 31, 41].…”
Section: Nutrients Digestibility Nitrogen Utilization and Chromium contrasting
confidence: 99%
“…Moreover, even rations containing Cr concentrations satisfying the need during a normal production period can become deficient in critical situations, such as advanced pregnancy, parturition, onset of lactation, weaning, and transport. Several researchers reported increased nutrient intake [7,8], whole tract apparent digestibility [9], and greater milk production [7,10] as a result of Cr supplementation. Cr supplementation decreased insulin concentration and increased glucose concentration and glucose insulin index in relation to cows not receiving Cr [11].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of effect of supplemental Cr on RR, PR, and RT might be attributed to the fact that the calves were not exposed to such a low ambient temperature that could alter these physiological variables. The findings of the present study on physiological variables are consistent with previous findings by KUMAR et al (2013), who also found no effect of Cr supplementation on the physiological responses of heat-stressed buffalo calves. DEKA (2014) conducted a feeding trial in Murrah buffaloes to study the effect of inorganic Cr supplementation on immune-endocrine parameters, nutrient utilization and productive performance in similar agro climatic conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased DMI around parturition may be due to increased parturition stress and increased size of the abdomen occupied by the fetus [16]. No effect of dietary Cr supplementation on DMI was reported by Kumar et al [17] who fed 0.5, 1.0, and 1.5 mg of inorganic Cr/kg DM to summer-exposed buffalo calves. Similarly, dietary addition of 1.6 mg of Cr/kg of DM in Holstein cows did not exert any effect on DMI [18].…”
Section: Dry Matter Intake and Body Condition Scorementioning
confidence: 96%
“…Blood Cr concentration might reflect to a certain extent the intake of this element, but in cases of excessive Cr intake, it is inappropriate to use the blood Cr concentration as an indicator of Cr status in animals [43]. A dose-dependent increase in plasma Cr concentration was observed by Kumar et al [17] in summer-exposed buffalo calves supplemented with inorganic Cr. A similar trend has also been observed in rats supplemented with different levels of Cr [44].…”
Section: Metabolic Responsesmentioning
confidence: 99%